Graph the linear function in questions 5 and 6. y=1/3x-4the pictures go in order from A to D
tess92 avatar

Answers

Answer 1
Answer:

Answer:

For y = 1/3x - 4

Step-by-step explanation:



Related Questions

Is 100 inches greater than 3yd 1 ft?
Suzanne needs material for her school project she buys 4.75 yards of material at $5.37 a yard what is the total cost of material round to the nearest cent a.$25.51 b.$30.61 c$255.08 d.$10.12
How do you solve 5x+7=3x-5
A MILKMAN SOLD TWO OF HIS BUFFALOES FOR RS.20,000. EACH ON ONE HE MADE A GAIN OF 5% AND ON THE OTHER A LOSS OF 10%. FIND HIS OVERALL GAIN OR LOSS.
What is 12/9 in simplest form

What is the volume of a cube with a side length of 5 cm? help asapA) 10 cm


B) 15 cm


C) 25 cm


D) 125 cm

Answers

V = a * b * c 
a,b,c- lengths of sides 
in here a=b=c=5cm 
V=5*5*5 = 125 cm^3

or 
V=a^3 = 5^3 =125 cm^3

A pair of inline skates, regularly priced at $180, is now on sale at a 30% discount. What is the sale price of the skates?

Answers

180 x (1-30%)
=180 x 0.7
=$126
so you divide it by 10 to get $18 (10%)
Then you do 18*3 = 54 (This is 30%)
Then you minus this from $180: 180-54= $126

What is 6 subtracted by 6099999

Answers

6099999-6= 6099993 is the answer
6099993 is the answer

PLEASE HELP ASAPIs the set of multiples of 4 closed under addition? Explain why or provide a counterexample if not. A. Yes, because the sum of any two multiples of 4 is also a multiple of 4. B. Yes, because the sum of any two multiples of 4 is also a multiple of 8. C. No, and a counterexample is –4 + (–8) = –12. D. No, and a counterexample is 26 + 16 = 42.

Answers

The answer is a. I hope that helped
this is kind of hard but the answer is its a because 4 is a multiple of 4  

Which expression is equivalent to the expression below?(6c^2+3c/-4c+2)/(2c+1/4c-2)

Answers

Answer:

-3c

Step-by-step explanation:

The given expression is:

((6c^(2)+3c)/(-4c+2))/((2c+1)/(4c-2))

We need to simplify this expression. The rational expression in the denominator can be multiplied to numerator by taking its reciprocal as shown below:

((6c^(2)+3c)/(-4c+2))/((2c+1)/(4c-2)) \n\n =(6c^(2)+3c)/(-4c+2) * (4c-2)/(2c+1)\n\n=(3c(2c+1))/(-(4c-2)) * (4c-2)/(2c+1)\n\n =-3c

Thus, the given expression in simplified form is equal to -3c

Answer:

-3c

Step-by-step explanation:

We are given that an expression

((6c^2+3c)/(-4c+2))/((2c+1)/(4c-2))

We have to find an expression which is equal to given  expression

Taking common 3c from nominator and -2 from denominator in dividened  and 2 common in divisor then we get

((3c(2c+1))/(-2(c-2)))/((2c+1)/(2(2c-1)))

(3c(2c+1))/(-2(2c-1))* (2(2c-1))/((2c+1))

By reciprocal divisor

By canceling same factor

Then ,we get

((6c^2+3c)/(-4c+2))/((2c+1)/(4c-2))

=-3c

35 = 45 - n;10,11,12 \\\\

Answers

35=45-n
we do not want negative n so we add n to both sides
n+35=45
now subtract 35 from both sides
n=10

This is an algebraic expression.The answer is 10,because 45-10=35.


Other Questions